Cuidados en el hogar relacionado a enfermedad diarreica aguda en menores de 5 años del Asentamiento Humano Amador Bartens Iquitos 2024 - Alvarado Yalta, Alexandra Angelica (2025)
The purpose was to determine the relationship between home and the EDA in children under 5 years of age in the Amador Bartens Human Settlement, Iquitos 2024. Quantitative, observational, descriptive, cross-sectional, correlational study; The population was made up of 30 mothers aged 5 <. The techniques used were: the survey and the home visit, and a questionnaire instrument (with validity 93.75% and reliability 81.57%). The results obtained were: 63.3% (19) manifested adequate care at home, in the presence of EDA and 36.7% (11) inadequate care. According to dimensions: 53.3% (16) of mothers manifested inadequate management of warning and protection signs and 46.7% (14) adequate management; 90.0% (27) of children received inadequate nutrition and hydration and 10.0% (3) adequate; 76.7% (23) had hygiene and an adequate environment and 23.3% (7) were inadequate. Regarding the number of episodes of acute diarrheal disease in children under 5 years of age, in the last 3 months: 43.4% (13) had one episode, 23.3% (7) two episodes, 23.3% (7) no episodes, and 10.0% (3) three episodes. When correlated, there is no significance between home care and ADD (p=0.543 > 0.05), nor with the following dimensions: management of warning signs and protection (p=0.312 > 0.05); food and hydration (p=0.285 > 0.05) and hygiene and environment (p=0.436 > 0.05). Concluding that mothers who provide adequate care at home to children under 5 years of age lead to a reduction in the number of episodes of ADD.